Challenges and solutions to providing surgery in Sierra Leone hospitals: a qualitative analysis of surgical provider perspectives. Issue 2 (1st February 2022) - Wilson, Spencer; Bah, Mohamed M; George, Peter; Caulker, Augustus; Holmer, Hampus; Leather, Andrew JM; Kamara, Thaim B
Abstract : Objective: This study aimed to use qualitative interviews with surgical providers to explore challenges and solutions to providing surgical and anaesthesia care in Sierra Leone's hospitals. Design: Data were collected through anonymous, semistructured interviews. We used a qualitative framework approach to analyse interview data and determine themes relating to challenges that were reported. Setting: A purposive sample of 12 hospitals was selected throughout Sierra Leone to include district and referral hospitals of varying ownership (private, non-governmental organisation and government). Participants: The most senior surgical provider available during each hospital site visit participated in a semistructured interview. A total of 12 interviews were conducted. Results: Providers described both challenges and solutions relating to the following categories: equipment and supplies, access to services, human resources, infrastructure, management and patient factors. These challenges were found to affect surgical care in hospitals by delaying surgical care, decreasing operative capacity and decreasing quality of care. Providers identified not only the root causes of these challenges, but also the varied workarounds and solutions they employ to overcome them. Conclusion: Surgical providers can offer important insights into challenges affecting surgical services in hospitals. Despite working in challenging environments with limited resources, providers have developed innovative solutions to improve surgical and anaesthesia care in hospitals in Sierra Leone. Qualitative research has an important role to play in improving understanding of the challenges facing surgeons in low-income countries.